Relationship between Differential Amounts of Prior Information and Security Return Variability - Lobo, Gerald J.; Mahmoud, Amal A. W. (Journal of Accounting Research, 1989)
Gerald J. Lobo, Amal A. W. Mahmoud, Relationship between Differential Amounts of Prior Information and Security Return Variability, Journal of Accounting Research, Vol. 27, No. 1 (Spring, 1989), pp. 116-134